Anti-Inflammatory Effects of Urocanic Acid Derivatives in Models Ex Vivo and In Vivo of Inflammatory Bowel Disease. (5th September 2012) - Kammeyer, Arthur; Peters, Charlotte P.; Meijer, Sybren L.; te Velde, Anje A.
Abstract : Urocanic acid (UCA) derivatives were tested for their anti-inflammatory activity in inflammatory bowel disease (IBD) in two models: ex vivo and an experimental mouse model. Ex vivo : inflamed colonic tissue was incubated in culture medium with or without the UCA derivatives. Biopsies, incubated with UCA derivatives, produced lower levels of proinflammatory cytokines IL-6 and IL-8 as compared to control biopsies. The same compounds also showed increased levels of IL-10, providing an additional indication for anti-inflammatory properties. In vivo : a combination of two imidazoles and a combination of two of their ethyl esters were administered to mice while colitis was induced by oral administration of dextran sodium sulfate (DSS). Some parameters did not show conclusive effects, but the imidazoles and their ethyl esters reduced the area of inflammation and the number of infiltrating neutrophils. Fibrosis and the sum of all histological aspects were reduced by the imidazoles, whereas the ethyl esters reduced the colon weight to length ratio. These results suggest that the UCA derivatives have anti-inflammatory effect on IBD. In addition, fine tuning of the ex vivo model may provide an elegant way to predict anti-inflammatory effects of potential drugs in humans, which may decrease the need for animal experiments.